Dishevelled-3 conformation dynamics analyzed by FRET-based biosensors reveals a key role of casein kinase 1 - Jakub Harnoš (Nature Portfolio, 2019)
Dishevelled (DVL) is the key component of Wnt signaling pathway that acts as a signaling hub. Here, authors study the conformational dynamics of DVL3 in vivo using their engineered FlAsH-based FRET biosensors and describe how Wnt activation opens DVL and facilitates Frizzled recruitment.